EFFECT OF GREEN HUMAN RESOURCE MANAGEMENT ON CORPORATE SUSTAINABILITY IN THE INSURANCE SECTOR - Adelugba Iyabode Abisola; Eze Benneth Uchenna; Olojede Paul; Eyanuku Julius Paul (Economic Review)
This study empirically examined the effect of Green Human Resource Management (HRM) on corporate sustainability in the Nigerian insurance industry. The study employed a survey technique through the administration of a structured questionnaire on employees of insurance companies in Nigeria. The population of this study comprised 20,000 employees and agents of insurance firms in Nigeria, which constituted the element of observation of this study. The sample size of the study was determined using Taro Yamane sample size determination formula, at 95% confidence level and 5% confidence interval, which gave a sample size of 377. A non-response rate of 40% was assumed, which increased the sample size to 527 (377+150). The findings reveal that Green HRM has a positive and significant effect on corporate sustainability, with coefficients and probability values of β1 =0.656, P-value < 0.05. This implies that Green HRM has a significant affect on corporate sustainability, The F-stat (52.673), P-value < 0.05 shows the fitness and overall significance of the regression model. The coefficient of determination (R2) suggested that 33.1% variation in corporate sustainability is accounted for by Green HRM. However, the model did not explain 66.9% of the variation in corporate sustainability, implying that there are other elements or factors associated with corporate sustainability, which were not captured in the current model. The study concludes that Green HRM is an important driver of corporate sustainability in the Nigerian insurance industry. Therefore, it is recommended that Nigerian insurance companies should utilize Green HRM towards enhancing their corporate sustainability